Promoting motivation and reducing stress in medical students by utilizing self-determination theory – a randomized controlled trial in practical psychiatry courses - Triebner, Nina; Sonnauer, Franziska; Rauch, Miriam; Kersten, Gian-Marco; Rauch, Christoph; Mestermann, Stefan; Bailer, Maximilian; Kornhuber, Johannes; Utz, Janine; Spitzer, Philipp (BMC Medical Education, 2024)
Background: Medical students experience high levels of stress and related mental health problems. Students’ autonomous and controlled motivation and their mental well-being are interconnected. This study aimed to investigate whether an innovative teaching concept based on self-determination theory (SDT) could improve students’ motivation and thereby reduce their stress levels, ultimately providing a healthier framework for learning. Methods: In a week-long practical psychiatry course for medical students, a new didactic concept was implemented in half the groups (n = 73) and compared with the preexisting concept (n = 75) as a randomized controlled trial (RCT). To promote the SDT-target factors of perceived autonomy, competence, and relatedness, the methods used included team building, exclusively positive feedback, group discussions, and choice in task distribution. Significant group differences in motivation, stress, performance, and their relationships were analyzed through t-tests, multiple linear regression analyses, mediation analyses, and hierarchical linear modeling (HLM) using questionnaires collected before (t0) and after (t1) the course, and students’ exam results (t2). Results: In the innovation group (n = 53), intrinsic motivation/interest (d = 0.41; p =.019) and perceived choice/autonomy (d = 0.33; p =.048) were greater than in the control group (n = 52). While autonomous regulation remained stable, the innovation group showed reduced controlled regulation (d = -0.36; p =.033) and reported significantly lower stress (d = -0.55; p =.003). The observed changes in motivation collectively mediated the stress reduction. However, students in the innovation group achieved lower exam scores, which seemed to result from the absence of critical feedback, but not from the observed differences in motivation or stress. Conclusions: This study demonstrated that enhancing intrinsic motivation through SDT-based teaching can effectively reduce stress in medical students. Exclusively strengths-based positive feedback may have hindered exam performance, but optimizing educational concepts to promote motivation and reduce stress will be a valuable step toward improving medical students’ mental well-being.
CRIS-Team Scopus Importer:2024-11-01
Keywords: Extrinsic motivation; Intrinsic motivation; Medical education; Psychiatry; Randomized controlled trial (RCT); Self-determination theory (SDT); Stress